(untitled) (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
This work presents a review of an algorithm to calculate the Mittag-Leffler function. In order to do it, we follow the definition of the Mittag-Leffler function in Refs. (GORENFLO; LOUTCHKO; LUCHKO, 2002; DIETHELM et al., 2005) and discuss some of its properties. Then, we revise the numerical algorithm in Ref. (DIETHELM et al., 2005) and plot some cases of Mittag-Leffler function performed. In addition, we discuss the accuracy and convergence of the presented algorithm.